2023
DOI: 10.12688/f1000research.129129.1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccines knowledge and acceptance among Indonesian adults in Java Island

Abstract: Background: To increase vaccination coverage, it is important to understand COVID-19 vaccination programs and respondents’ acceptance. Therefore, this study aimed to measure respondents’ knowledge of the COVID-19 vaccine and its acceptance among Indonesian adults in Java. Methods: A web-based survey was distributed through social media on self-claimed knowledge, risk and benefits of the vaccine, as well as respondents’ acceptance and experiences of the vaccination. The survey period was from March to July 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…As of 19 November 2022, Indonesia vaccination coverage was 75.98 and 63.74%, for the first dose and second dose, respectively [ 45 ]. A study involving 910 Indonesian adults showed that younger ages, having better knowledge on vaccination, and having medical background were more likely to accept the COVID-19 vaccination program [ 28 ]. COVID-19 vaccination program also concluded to reduce distress including fear of infection, hospitalization and mortality due to COVID-19 as reported in 8090 US adults [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of 19 November 2022, Indonesia vaccination coverage was 75.98 and 63.74%, for the first dose and second dose, respectively [ 45 ]. A study involving 910 Indonesian adults showed that younger ages, having better knowledge on vaccination, and having medical background were more likely to accept the COVID-19 vaccination program [ 28 ]. COVID-19 vaccination program also concluded to reduce distress including fear of infection, hospitalization and mortality due to COVID-19 as reported in 8090 US adults [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine hesitancy and availability also play a major role in the high mortality during the second wave of the COVID-19 pandemic [ 27 ]. At the beginning of the COVID-19 vaccination program in Indonesia, the acceptance rate is 64.8% and increased to more than 90% during the Delta wave COVID-19 pandemic [ 28 ]. The governments' strategies to reduce SARS-CoV-2 transmission, such as lockdowns, strict regulation of transportation and wearing masks, vaccination program, etc.…”
mentioning
confidence: 99%